Investigation of smoothness conditions on the boundary for the strong linear convexity of a domain - Mel’nik, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We construct a counterexample for the hypothesis that the strong linear convexity of a domain follows from the linear convexity if the set of singularities does not split the boundary.